Tracking Progress Toward Sustainable Energy for All in Sub-Saharan Africa - Portale, Elisa; de Wit, Joeri (2014)
In declaring 2012 the 'International Year of Sustainable Energy for All,' the UN General Assembly established three global objectives to be accomplished by 2030: to ensure universal access to modern energy services, to double the 2010 share of renewable energy in the global energy mix, and to double the global rate of improvement in energy efficiency relative to the period 1990-2010 (SE4ALL 2012). The SE4ALL objectives are global, with individual countries setting their own national targets in a way that is consistent with the overall spirit of the initiative. Because countries differ greatly in their ability to pursue the three objectives, some will make more rapid progress in one area while others will excel elsewhere, depending on their respective starting points and comparative advantages as well as on the resources and support that they are able to marshal. To sustain momentum for the achievement of the SE4ALL objectives, a means of charting global progress to 2030 is needed. The World Bank and the International energy agency led a consor¬tium of 15 international agencies to establish the SE4ALL Global Tracking Framework (GTF), which provides a system for regular global reporting, based on rigorous, yet practical, given available databases, technical measures. This note is based on that frame¬work (World Bank 2014). SE4ALL will publish an updated version of the GTF in 2015.